THE RELATIONSHIP BETWEEN SELF-REGULATION, TIME MANAGEMENT, AND STUDENTS PHYSICS LEARNING OUTCOMES CLASS XI MIA IN SMA NEGERI 6 TAKALAR (International Conference on Social and Islamic Studies, 2022)
This research is an ex post facto research that aims to find out how: (1) the relationship between self regulation and physics learning outcomes in class XI MIA students at SMA Negeri 6 Takalar (2) the relationship between time management and physics learning outcomes in class XI MIA students at SMA Negeri 6 Takalar (3) the relationship between self regulation and time management and physics learning outcomes in class XI MIA students at SMA Negeri 6 Takalar. The research design used is correlational. The population of this study was all students of class XI MIA SMA Negeri 6 Takalar amounting to 100 people divided into 3 classes. The sample of this research is 85 people if the desired confidence of the sample to the population is 95% or an error rate of 5% the number of samples taken is 85% students. The results of the study show that; 1) based on Correlation Coefficien = 0,013 there is a very weak relationship between self regulation and physics learning outcomes and is obtained = 0,4659 = 3,9, which shows there is no significant relationship between self regulation and physics learning outcomes in students XI MIA SMAN 6 Takalar because the value obtained at dari 0,05. 2) based on Correlation Coefficien = 0,074 there is a very weak relationship between time management and physics learning outcomes and is obtained = 0,4659 =3,9, which shows there is no significant relationship between time management and physics learning outcomes in students XI MIA SMAN 6 Takalar because the value obtained at dari 0,05. 3) there is no significant relationship between self regulation and time management and student learning outcomes XI MIA SMAN 6 Takalar with grades sig. 0,281 and obtained = 0,0024 = 3,1. Because the value obtained at dari 0,05. Research implication of the result of this study are expected to be tried again in deoth with more samples in order to provide more relevant information about the relationship between self regulation and time management and physics learning outcomes for future research.